2006
DOI: 10.1093/imamat/hxl016
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and convection of gaseous and fine particulate from a chimney

Abstract: Particle dispersion from a high chimney is considered and an expression for the subsequent concentration of the particulate deposited on the ground is derived. We consider the general case wherein the effects of both diffusion and convection on the steady state ground concentration of particulate are incorporated. Two key parameters emerge from this analysis: α, the ratio of diffusion to convection, and λ, the nondimensionalised surface mass transfer rate. We also solve the inverse problem of recovering these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…2 ) x, y = y/H, z = z/H, and C = (uH 2 /Q) C (a similar rescaling of variables is used in other studies such as [25] and [31]). Compare the relative sizes of terms in the equation for typical values of the parameters given in Table 3.1, and consequently show that neglecting the diffusion term in the x-direction is a reasonable approximation.…”
Section: S( X) = Q δ(X) δ(Y) δ(Z −mentioning
confidence: 99%
See 1 more Smart Citation
“…2 ) x, y = y/H, z = z/H, and C = (uH 2 /Q) C (a similar rescaling of variables is used in other studies such as [25] and [31]). Compare the relative sizes of terms in the equation for typical values of the parameters given in Table 3.1, and consequently show that neglecting the diffusion term in the x-direction is a reasonable approximation.…”
Section: S( X) = Q δ(X) δ(Y) δ(Z −mentioning
confidence: 99%
“…Llewelyn [22] solved a time-dependent version of the atmospheric dispersion problem and showed that his solution reduces asymptotically to Ermak's at steady state. An alternative derivation using complex variable techniques was used by MacKay, McKee, and Mulholland [25] for the problem with deposition but no settling. Interestingly, similar solutions have been derived for other problems arising, for example, in diffusion of ligand molecules in a protein matrix [27].…”
Section: Other Generalizationsmentioning
confidence: 99%
“…The heights of the four contaminant sources, corrected for plume rise, are H s = [15,35,15,15] while the nine receptors are located at heights h r = [0, 10,10,1,15,2,3,12,12]. The dustfall jars are glass containers in the shape of circular cylinders having a diameter of 0.162 m, and so the area parameter used in the deposition calculation in Eq.…”
Section: Parameter Values and Wind Datamentioning
confidence: 99%
“…Another related stream of research has focused on solving the corresponding inverse problem, whereby measurements of particulate concentrations or ground-level depositions are given and the aim is to determine information about the location or efflux rate of contaminant sources. Inverse methods based on Gaussian plume type solutions have been developed by a number of authors in this context including Jeong et al [13] and Hogan et al [14], while MacKay et al [15] developed an alternate solution approach using complex variable theory. Other researchers have applied a more direct computational approach by solving the nonlinear governing equations using methods based on Kalman filtering [16], Lagrangian particles [17], Bayesian techniques [18,19], or by integrating the equations backward in time [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation